The Impact of Baron Fishermen's Activities on the Socio-Economic Life of Kemadang Village Residents, 2011-2017 - Pangesti, Fahida Aprilia; Susilowati, Endang (Journal of Maritime Studies and National Integration, 2024)
This study examines the impact of fishing activities on Baron Beach on the socioeconomic conditions of the residents of Kemadang Village from 2011 to 2017. Using historical methods, this study analyzes how the transition from land-based agriculture to fishing has affected income, welfare, and infrastructure development in the region. The results show that the abundant fish production at Baron Beach has significantly increased fishermen's income, who now earn 2-3 times a week compared to the twice-a-year income from agriculture. This income increase has directly improved living standards, such as increased ownership of goods, access to higher education for fishermen's children, and improved housing quality from semi-permanent to permanent structures. Fishing activities have also driven improvements in facilities and infrastructure, including the construction of a lighthouse, renovation of the fish auction building, relocation of vendors, and an increase in the number of boats from 51 to 55 units. This study highlights the socio-economic transformation brought about by the shift to fishing as the primary livelihood in Kemadang Village.